Fukcja perykop 2, 1-5; 2, 20-22; 6, 8-10; 10, 11-16 w Księdze Sędziów. (Z zagadnień problematyki redakcyjnej Księgi) - Szwarc, Urszula (The Biblical Annals, 2017)
The paper consists of condensed analysis of four God’s utterances (Judg 2, 1-5; 2, 20-22; 6, 8-10; 10, 11-16) and lines which are their proximate context. In the final part of the paper one finds a juxtaposition of the author’s findings which can be put in the following way: the texts foregoing the pericopes in question and those which immediately follow them are markedly different; their similarity a purely superficial; the lines 2,1-5; 2, 20-22; 6, 8-10; 10,11-16 are characterized by a literary different approach; in view of their content and vocabulary, they are only partially kindred. Probably they were written by different authors and not at the same time. What they have in common is their deuteronomistic composition.